Water-resistant AgBiS2 colloidal nanocrystal solids for eco-friendly thin film photovoltaics. Issue 19 (8th May 2019) - Oh, Jae Taek; Bae, Sung Yong; Ha, Su Ryong; Cho, Hongjoo; Lim, Sung Jun; Boukhvalov, Danil W.; Kim, Younghoon; Choi, Hyosung
Abstract : The AgBiS2 nanocrystal solar cells exhibit no drop in their device performance before and after the water treatment, suggesting that AgBiS2 nanocrystal solids are highly water-resistant. Abstract : Lead-free, water-resistant photovoltaic absorbers are of significant interest for use in environment-friendly and water-stable thin film solar cells. However, there are no reports on the water-resistance characteristics of such photoactive materials. Here, we demonstrate that silver bismuth sulfide (AgBiS2 ) nanocrystal solids exhibit inherent water resistance and can be employed as effective photovoltaic absorbers in all-solid-state thin film solar cells that show outstanding air and moisture stabilities under ambient conditions. The results of X-ray photon spectroscopy (XPS) and X-ray diffraction (XRD) analyses show that there is no change in the chemical composition and crystal structure of the AgBiS2 nanocrystal solids after a water treatment. Based on these results, AgBiS2 nanocrystal solar cells are fabricated. These devices also do not show any drop in performance after a water treatment, confirming that the AgBiS2 nanocrystal solids are indeed highly water-resistant. In contrast, lead sulfide (PbS) colloidal quantum dot (CQD) solar cells show significant decrease in performance after a similar water treatment. Using XPS analysis and density functional theory (DFT) calculations, we confirm that the iodine removal and the surface hydroxylation of the water-treated PbS CQD solids are the primary reasons for the observed decrease in the device performance of the CQD solar cells.